Design, simulation, and static testing of an eco-friendly prosthetic foot using ramie-PLA composite - Sopiyan, Iyan; Soemardi, Tresna P.; Purnomo, Herry; Polit, Olivier (Universitas Negeri Padang, 2025)
This study developed a sustainable lower-limb prosthetic prototype using biodegradable ramie fiber-reinforced PLA composite as its primary material. The design specifically addresses the needs of individuals with limb amputation while prioritizing environmental sustainability. PLA-based composites for structural biomedical applications—particularly those in lower-limb prosthetics—must meet rigorous mechanical and fatigue performance requirements under repetitive loading. This study investigates the development of a transtibial prosthetic foot prototype using a quasi-isotropic lay-up prepreg ramie-PLA composite fabricated via the hot press method. Material characterization was conducted per ASTM standards, and the design was evaluated using the Finite Element Method (FEM). The prototype underwent static testing according to ISO 22675 with a user load criterion. The laminate exhibited an ultimate tensile strength of 48.36 ± 0.95 MPa, an elastic modulus of 4.125 ± 0.25 GPa, and a flexural strength of 62.06 ± 3.43 MPa. FEM results showed that all normal and shear stresses during heel strike (17.78 MPa and 1.71 MPa) and toe-off (12.38 MPa and 5.69 MPa) phases remained below fatigue limits. Experimental static stresses were heel strike (12.72 MPa) and toe-off (20.09 MPa), both within safe operational limits. These findings highlight the structural viability and environmental sustainability of ramie-PLA composites, positioning them as a promising material for next-generation prosthetic foot development.